2022
DOI: 10.2196/30807
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App to Improve Oral Anticoagulation Adherence in Patients With Atrial Fibrillation: Prospective Observational Study

Abstract: Background Poor adherence to oral anticoagulation in elderly patients with atrial fibrillation (AF) has been shown to negatively impact health care costs, morbidity, and mortality. Although various methods such as automated reminders, counseling, telephone support, and patient education have been effective in improving medication adherence, the burden on health care providers has been considerable. Recently, an attempt has been made to improve medication adherence without burdening health care prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis showed that studies on the use of mobile applications were conducted in the USA (n=7) ( 30 - 36 ), Sweden (n=3) ( 37 - 39 ), Republic of Korea (n=1) ( 40 ), Brazil (n=1) ( 41 ), Norway (n=2) ( 42 , 43 ), Switzerland (n=1) ( 44 ), Belgium (n=1) ( 45 ), China (n=9) ( 22 , 46 - 53 ), Romania (n=1) ( 54 ), Japan (n=1) ( 55 ), Finland (n=1) ( 24 ), France (n=1) ( 56 ), New Zealand (n=1) ( 57 ), Iran (n=2) ( 58 , 59 ), Georgia (n=1) ( 60 ), Spain (n=2) ( 61 , 62 ), Palestine (n=1) ( 63 ) and Germany (n=3) ( 64 - 66 ). Two studies were conducted simultaneously in India (n=2) ( 67 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…By category, the research was focused on the following areas: mobile applications for diagnostic purposes (for example, ECG recording ( 30 ), assessment of heart rate ( 31 , 33 , 44 , 65 ). Some studies were carried out to validate the system for urgent care alarm ( 37 ), lifestyle changes ( 43 , 45 , 53 , 62 , 65 ), adherence to treatment ( 35 , 38 , 41 , 47 , 48 , 51 , 53 , 55 , 59 , 60 , 63 , 64 , 67 , 68 ), and physical activity of the patients ( 22 , 32 , 34 , 41 , 45 , 62 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective observational study conducted by Senoo et al [ 30 ] showed promising results in terms of adherence improvement in older adult patients with AFib. The Medisafe medication management app is a medication management platform, which includes the name of the medication and the dose.…”
Section: Resultsmentioning
confidence: 99%
“…To assist clinicians with individualizing warfarin therapy, we simulated individualized warfarin dosing based on LSTM_INR. The trend of using mobile applications or electronic systems for anticoagulation is likely more suitable for long-term individualized therapy and anticoagulant self-management ( 27 , 28 ). Thus, we developed an application (AI-WAR) in which we embedded these were embed in.…”
Section: Discussionmentioning
confidence: 99%